2016
DOI: 10.1080/13696998.2016.1198355
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of spinal muscular atrophy

Abstract: Individuals with SMA have a high degree of morbidity, particularly those diagnosed during infancy. SMA patients have significant medical expenditures and high utilization of healthcare services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 13 publications
5
50
0
5
Order By: Relevance
“…In accordance with findings from the current study, previous studies have consistently found SMA to be associated with high HRU and healthcare costs [11][12][13][14][15][16][17][18][19] , including a few recent claims-based studies that evaluated the economic burden of SMA [12][13][14] . For example, Dabbous et al 13 conducted a retrospective analysis of patients with SMA1 using the Quintiles IMS's PharMetrics Plus Health Plan Claims Database (February 2011-November 2016).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In accordance with findings from the current study, previous studies have consistently found SMA to be associated with high HRU and healthcare costs [11][12][13][14][15][16][17][18][19] , including a few recent claims-based studies that evaluated the economic burden of SMA [12][13][14] . For example, Dabbous et al 13 conducted a retrospective analysis of patients with SMA1 using the Quintiles IMS's PharMetrics Plus Health Plan Claims Database (February 2011-November 2016).…”
Section: Discussionsupporting
confidence: 91%
“…who likely had SMA1) had particularly high healthcare costs that amounted to $159,227 PPPY, those aged 2-18 years had PPPY costs of $105,206, and those aged >18 years had PPPY costs of $39,355. Similarly, Armstrong et al 12 conducted a retrospective analysis of pediatric patients (<18 years) with SMA using US Department of Defense Military Healthcare System (MHS) data contained within the MHS Data Repository (2003-2012). The authors reported that PPPY healthcare costs were significantly higher for patients diagnosed in their first year of life (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(8,9) Given the rarity of SMA, the direct and indirect costs per capita are close to $200,000. (10,11) The latest treatment patterns and economic study on patients with SMA found signi cantly higher healthcare utilization and costs than the general population. (12) Multiple studies have found substantially higher costs for patients with SMA compared to healthy populations.…”
Section: Introductionmentioning
confidence: 99%